THE EFFECT OF THE APPLICATION OF GRAPHIC ORGANIZER STRATEGIES ON THE ABILITY TO ANALYZE FAIRY TALES IN CLASS IV SDN 37 PEKANBARU - Fatimah Ully Artha Sinaga (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Graphic organizer is a strategy that cordinates ideas and cooncepts into visual form. The purpose of this research was to determine the ability of students to analyze fairy tales using graphic organizer strategies.The research methd used is quasi experimental research.The ability of students to analyze fairy tales using graphic organizer can be proven from results of t-test with signifikan level of 5% ( 95% degrees of confidence) obtained t-counts (7.875) >t tables (2.080) and sig (0.019) < 0.05. The value of t-count > t-table or sig.< 0.05 shos that the ability to analyze fairytale stories of the two groups is significantly different. This is also supported differences in the average value of the posttest results of analyzing the students fairy tale in the experimental group anda the control group.the experimental group got an average value of 94.48, while the controol group obtained an average value of 62.30, so that it could be conluded that there was a significant influence on the use of a graphic organizerstrategy on the ability to analyze fairytale stories in grade IV SDN 37 Pekanbaru.